N4-acetylcytidine modification of ITGB5 mRNA mediated by NAT10 promotes perineural invasion in pancreatic ductal adenocarcinoma - Leyi Huang; Yanan Lu; Rihua He; Xiaofeng Guo; Jiajia Zhou; Zhiqiang Fu; Jingwen Li; Jianping Liu; Rufu Chen; Yu Zhou; Quanbo Zhou (Journal of Experimental & Clinical Cancer Research)
Abstract Background Perineural invasion (PNI) is a hallmark feature of pancreatic ductal adenocarcinoma (PDAC), which occurs at a high incidence and significantly contributes to PDAC lethality and poor survival. Despite its prevalence and association with poor prognosis, the molecular mechanisms underlying PNI in PDAC remain unclear. Methods We investigated clinical samples from two cohorts by UPLC/MS-MS to profiled significantly altered chemical RNA modifications in PDAC tissues with PNI lesions. Dorsal root ganglion coculture systems and sciatic nerve injection models validated PNI ability. We combined RNA-seq, acRIP-seq and ac4C-seq with CRISPR-based techniques to explore the regulatory mechanism of ac4C modification on the integrin beta 5 (ITGB5) transcript. Result We reported that N4-acetylcytidine (ac4C) is a significantly altered chemical RNA modification in PDAC tissues with PNI lesions. In vitro and in vivo models demonstrated that tumor cells overexpression of N-acetyltransferase 10 (NAT10), the writer enzyme of mRNA ac4C modification, enhances PNI in PDAC. Further analysis revealed decreased ac4C levels on transcripts of the focal adhesion pathway, particular on ITGB5, in NAT10-knockdown PDAC cells. This ac4C modification in the CDS region of ITGB5 mRNA promotes its stability, subsequently activating the ITGB5-pFAK-pSrc pathway. CRISPR-based analysis further confirmed the crucial role of NAT10-mediated ac4C modification in regulating ITGB5 expression. Combining small-molecule inhibitors targeting NAT10 and focal adhesion kinase (FAK) significantly attenuated PNI in vivo. Conclusion Our findings reveal a previously unrecognized ac4C-mediated epigenetic mechanism in PNI and propose a novel therapeutic strategy to improve survival in PDAC patients. One-sentence summary NAT10 promotes PNI via ac4C modification in PDAC.